Phenomenology of mathematics learning in high school students on relations and functions: An innovative approach based on conceptual innovation (BIS Humanities and Social Science, 2026)
This study aims to explore the learning experiences of high school students in studying the topic of relations and functions in mathematics. Employing a qualitative approach grounded in phenomenological methodology, the research focuses on students’ subjective understanding of the classroom learning process. Data were collected through elicitation techniques, direct classroom observation, and documentation, involving four informants: three 11th-grade students and one mathematics teacher at SMA 1 Muhammadiyah Ponorogo. Data analysis was conducted thematically following the Miles and Huberman model, which includes the stages of data reduction, data display, and conclusion drawing. The findings reveal three main themes that shape students’ learning experiences: (1) the meaning of learning mathematics for students, and (2) interaction and participation in the learning process. Students interpret mathematics learning differently depending on their level of understanding and their comfort with social interactions in the classroom. Students who understand the material tend to feel more confident during the learning process, whereas those who experience difficulties are more likely to be passive and hesitant to ask questions. In conclusion, meaningful mathematics learning should not only emphasize cognitive aspects but also consider the emotional and social dimensions of students’ learning experiences.